Social Fiqh and Its Implications for Community Life in Society 5.0 - Rasyid, Arbanur (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
This paper aims to analyze and examine the developmental model of social fiqh in the era of society 5.0 and its implications for the social life of modern society in the 21st century AD. The research method uses a literature review by collecting various appropriate and supportive literature on social fiqh studies, such as the works of KH Sahal Mahfudz and KH Ali Yafi. The study results show that social fiqh in the 5.0 era will increase the ease of access and progress in people's lives concerning social, cultural, economic, and political issues by prioritizing the values of the public benefit. The development of social fiqh in the era of society 5.0 is a step to alleviate the increasingly complex problems of the people. Social fiqh also educates and guides humans to become advanced, independent, prosperous, tolerant, moderate, balanced, and just human beings.